-2348-0653 A STUDY ON THE MICROFINANCE THROUGH KUDUMBASHREE UNITS - Asoora . K (International Journal of Business and Administration Research Review, 2014)
This study aims to analyze the impact of Microfinance through KDS, and purpose of obtaining Microfinance. The researcher applied Paired t test, Z test, ANOVA, Weighted Average, Rank. Karl Pearson’s Correlation coefficient, and Percentage analysis. Based on the data analysis findings are arrived. The purpose of this study is to gain a better knowledge on the effectiveness of Microfinance and forecast future plan for the development of KDS and its members.